First clinical report of 179 surrogacy cases in the UK: implications for policy and practice. Issue 4 (October 2022) - Horsey, Kirsty; Gibson, Grace; Lamanna, Giuseppina; Priddle, Helen; Linara-Demakakou, Elena; Nair, Shailaja; Arian-Schad, Mimi; Thackare, Hemlata; Rimington, Michael; Macklon, Nicholas; Ahuja, Kamal
Abstract: Research question: What implications for policy and practice can be derived from outcomes and trends observed across 8 years of a surrogacy programme in two UK-regulated IVF centres (London, Cardiff)? Design: Retrospective cohort study analysing surrogacy treatments undertaken between 2014 and September 2021. Results: Surrogacy continues to rise in popularity in the UK despite the inability of those supporting safe and professional practice to advertise to recruit surrogates. In two IVF centres regulated by the Human Fertilisation and Embryology Authority (HFEA), both the number of surrogacy treatments and the proportion of those undertaken on behalf of same-sex male intended parents increased year on year in the period studied. From a cohort of 108 surrogates, 71 babies were born to 61 surrogates (with five pregnancies ongoing) by February 2022. No statistically significant difference in live birth rates (LBR) was observed between the heterosexual couples and same-sex male couples. Sample sizes of single and transgender intended parents were too small ( n < 5) to compare. The use of vitrified oocytes in surrogacy treatments has increased year on year, while fresh oocyte use has declined since peaking in 2019. There was no significant difference in LBR between fresh and vitrified oocyte usage across the cohort. Conclusions: The number of surrogacy treatments steadily increased, with clear evidence that the proportion of same-sex male couples accessing surrogacy is a major contributor to this growth. Vitrified/warmed oocyte use now outstrips the use of fresh oocytes in the surrogacy treatment cycles studied here. The results represent a strong basis for supporting the liberalization of regulatory reform expected to be introduced in the UK later in 2022.